Effect of short‐term semen storage in salmon (Oncorhynchus mykiss) on sperm functional parameters evaluated by flow cytometry. (9th April 2014) - Trigo, P.; Merino, O.; Figueroa, E.; Valdebenito, I.; Sánchez, R.; Risopatrón, J.
Summary The short‐term storage of salmonid semen is a viable method for in vitro fertilisation. Previous studies have found that short‐term storage affects sperm motility, compromising quality and fertilising capacity. However, the functional characteristics of the spermatozoa of O. mykiss during storage time and its relation to the spawning period are little known. This study was designed to evaluate the effects of in vitro short‐term storage on sperm functional parameters in O. mykiss, determined by flow cytometry. Semen samples of the first spawning – undiluted (SSD) and diluted (SD) (Storfish® 1 : 2v/v; IMV AI solutions, France) – were stored at 4 °C for 14 days. Motility, viability (PMI: plasma membrane integrity) and mitochondrial membrane potential (ΔΨM) were assessed. On the fifth day of storage, spermatozoa showed a motility >70% (SSD: 78.3% versus SD 85.0%), PMI (81.5% SSD/87.2% SD) and ΔΨM (72.5% SSD/SD 80.0%) (P < 0.05). However, a significant decline in the percentage of all functional parameters (P < 0.05) was observed after 5 days of storage for all samples of both undiluted (SSD) and diluted semen. In conclusion, the results here provide new data on O. mykiss sperm quality with respect to in vitro short‐term storage evaluated by flow cytometry.